Paulownia fortunei L.: Growth and phenology under temperate conditions of Kashmir - Masoodi, T.H.; Banyal, R.; Masoodi, N.A. (Indian Journal of Agroforestry, 2020)
The study was conducted to address the issues pertaining for introduction along with phenological behavior of Paulownia fortunei in the landscape of Kashmir. Paulownia fortunei having wide ecological amplitude thrives well in the temperate conditions of Kashmir. Propagation study reveals that root cuttings of 13 or 15cm must be taken for production of large sized planting material. The plant height, collar diameter, leaf area and total root length increased with increase in size of root cuttings. However, 13cm long root cuttings found to yield a multiplication rate 40 times from the root of single ETP. P fortunei found to establish comparatively better to some extent and eight years old plants attained an average height of 9.80m with 24.50cm diameter in temperate conditions. The plantation took on an average two more years to attain the similar growth parameters in Kashmir region, as compared to its natural distribution. The two-storied crown was formed from sixth year onward. The crown expansion decreased from six times in the first year to 0.07 times at the age of eighth year. Paulownia fortunei responded somewhat slower in all the phenophases like leaf emergence, canopy formation, leaf shedding, flower bud formation, fruit setting, fruit ripening and seed dispersal in temperate conditions compared to tropical and sub-tropical conditions. Inflorescence is pedunculate or sub-sessile cyme having 2 to 5 flowers in bunches. The colour of the flower is purplish white and is about 8.5cm in length. All the phenophases of the tested spp. are found to in consonance with the phenological events of the agricultural crops under temperate conditions. The study proven beyond any doubt that P fortunei may be seen as one of the economically viable option to the farming community of Kashmir in the coming period.